T-Cell Responses to Immunodominant Listeria Epitopes Limit Vaccine-Directed Responses to the Colorectal Cancer Antigen, Guanylyl Cyclase C - Flickinger, John C.; Singh, Jagmohan; Yarman, Yanki; Carlson, Robert D.; Barton, Joshua R.; Waldman, Scott A.; Snook, Adam E. (Frontiers in Immunology, 2022)
The Gram-positive bacterium Listeria monocytogenes (Lm) is an emerging platform for cancer immunotherapy. To date, over 30 clinical trials have been initiated testing Lm cancer vaccines across a wide variety of cancers, including lung, cervical, colorectal, and pancreatic. Here, we assessed the immunogenicity of an Lm vaccine against the colorectal tumor antigen GUCY2C (Lm-GUCY2C). Surprisingly, Lm-GUCY2C vaccination did not prime naïve GUCY2C-specific CD8+ T-cell responses towards the dominant H-2Kd-restricted epitope, GUCY2C254-262. However, Lm-GUCY2C produced robust CD8+ T-cell responses towards Lm-derived peptides suggesting that GUCY2C254-262 peptide may be subdominant to Lm-derived peptides. Indeed, incorporating immunogenic Lm peptides into an adenovirus-based GUCY2C vaccine previously shown to induce robust GUCY2C254-262 immunity completely suppressed GUCY2C254-262 responses. Comparison of immunogenic Lm-derived peptides to GUCY2C254-262 revealed that Lm-derived peptides form highly stable peptide-MHC complexes with H-2Kd compared to GUCY2C254-262 peptide. Moreover, amino acid substitution at a critical anchoring residue for H-2Kd binding, producing GUCY2CF255Y, significantly improved stability with H-2Kd and rescued GUCY2C254-262 immunogenicity in the context of Lm vaccination. Collectively, these studies suggest that Lm antigens may compete with and suppress the immunogenicity of target vaccine antigens and that use of altered peptide ligands with enhanced peptide-MHC stability may be necessary to elicit robust immune responses. These studies suggest that optimizing target antigen competitiveness with Lm antigens or alternative immunization regimen strategies, such as prime-boost, may be required to maximize the clinical utility of Lm-based vaccines.